Educational Needs and Barriers for African Refugee Students in Manitoba - Kanu, Yatta (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
This study investigated the educational needs and barriers for diverse African refugee students in two inner‐city high schools in Manitoba. Forty African refugee students, two principals, eight teachers, four parents, and four community leaders participated in the study. Five focus groups, individual interviews, and school and classroom ob‐ servations were used to collect data. Results revealed that academic, economic, and psychosocial challenges facing African refugee students adversely affected their abil‐ ity to integrate and cope well in school, thereby significantly reducing their socio‐ economic opportunities. Policy implications and urgent reform measures such as forgiveness of refugee resettlement loans and better housing in safer neighbourhoods are suggested. Key words: War‐affected African refugee students educational needs, educational barriers,refugee student support programs, social integration and educational suc‐ cess. Dans cet article, l’auteure analyse les besoins en éducation et les difficultés des élèves réfugiés venant du continent africain et fréquentant deux écoles secondaires situées dans des quartiers pauvres au Manitoba. Quarante élèves africains, tous des réfugiés, deux directeurs d’école, huit enseignants, quatre parents et quatre leaders communau- taires ont participé à cette étude. Cinq groupes de discussion, des entrevues indivi- duelles et des séances d’observation dans l’école et en classe ont été utilisés pour ré- unir les données. Les résultats indiquent que les défis scolaires, économiques et psy- chosociaux auxquels font face ces jeunes africains réfugiés affectent leur aptitude à bien s’intégrer et s’adapter à l’école, ce qui a pour effet de réduire nettement leurs possibilités socioéconomiques. L’auteure suggère des changements au niveau des politiques ainsi que des mesures de réforme urgentes, telles l’exonération du rem- boursement des prêts consentis pour l’aide à l’établissement des réfugiés et l’amélioration des conditions de logement et ce, dans des quartiers plus sûrs. Mots clés : besoins en éducation des élèves réfugiés provenant de pays africains en guerre, obstacles à l’éducation, programmes d’assistance à l’intention des élèves réfu- giés, intégration sociale, réussite scolaire